Saxagliptin Efficacy and Safety in Patients with Type 2 Diabetes Mellitus Stratified by Cardiovascular Disease History and Cardiovascular Risk Factors: Analysis of 3 Clinical Trials. Issue 6 (October 2014) - Cook, William; Minervini, Gianmaria; Bryzinski, Brian; Hirshberg, Boaz
Abstract : Abstract Objective: To test the effectiveness and safety of saxagliptin 5 mg/d in patients with type 2 diabetes mellitus (T2DM) with and without history of cardiovascular disease (CVD) or cardiovascular (CV) risk factors.Methods: The authors conducted a post hoc analysis of data from 3 randomized studies that compared saxagliptin versus placebo as initial combination therapy with metformin for 24 weeks (N = 648) and versus placebo as an add-on to insulin with and without metformin for 24 weeks (N = 455), and assessed noninferiority to glipizide as an add-on to metformin for 52 weeks (N = 858). Efficacy outcomes were the adjusted mean change from baseline in glycated hemoglobin (HbA1c ) level, fasting plasma glucose concentration, and body weight and the proportion of patients achieving an HbA1c level < 7%. Pairwise comparisons were performed in subgroups with 1) history/no history of CVD, 2) ≥ 2 versus 0 to 1 CV risk factors, 3) hypertension/no hypertension, and 4) statin use/no statin use. Adverse events (AE) and hypoglycemia were monitored.Results: In the initial combination therapy study, reductions in HbA1c level from baseline were greater with saxagliptin versus placebo in all subgroups (difference [saxagliptin - placebo], −0.38% to −0.67%). In the add-on to insulin ± metformin study, differences in adjusted mean change in HbA1c level versus placebo ranged from −0.23% to −0.58% across subgroups. In the noninferiority to glipizide study, adjusted mean changes in HbA1c level were comparable between saxagliptin and glipizide, across subgroups (difference, 0.08%–0.21%). No evidence suggested clinically relevant treatment-by-subgroup interactions in pairwise comparison. Incidences of ≥ 1 AE were comparable across subgroups. Incidences of confirmed hypoglycemia with saxagliptin were 0 in both metformin add-on studies and 1.2% to 7.8% with saxagliptin + insulin ± metformin.Conclusion: In patients with T2DM, saxagliptin 5 mg/d was similarly effective in improving glycemic control, with an AE profile similar to that of placebo, irrespective of CVD history, number of CV risk factors, hypertension, or statin use.Trial registration: www.ClinicalTrials.gov identifiers: NCT00327015, NCT00575588, NCT00757588